1983
DOI: 10.1161/01.hyp.5.6.935
|View full text |Cite
|
Sign up to set email alerts
|

Influence of captopril treatment on angiotensin II receptors and angiotensinogen in the brain of spontaneously hypertensive rats.

Abstract: SUMMARY The brain renin-angiotensin system (RAS) has been suggested as contributing to the pathogenesis of spontaneous hypertension in rats. Brain angiotensinogen-and angiotensin II (AII)-sensitive neurons were therefore investigated in stroke-prone spontaneously hypertensive rats (SHRsp) and in Wistar-Kyoto (WKY) rats with and without treatment by captopril (CAP). Angiotensinogen was decreased in the anterior hypothalamus but increased in the cortex, the hippocampus, and cerebellum of SHR-sp. There were no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 38 publications
(29 reference statements)
4
8
0
Order By: Relevance
“…These findings are in agreement with our previous observations, 22 which also showed that lifetime-captopril-treated SHR had decreased brain Ang II binding, suggesting a depressed angiotensinergic system in the brain. Our results are also consistent with those of Schelling and Felix, 32 who showed a decrease in the sensitivity of Ang II receptors to iontophoretically applied Ang II in septal neurons of SHRSP with lifetime captopril treatment. 32 In summary, lifetime oral captopril treatment prevented the development of hypertension in spontaneously hypertensive rats.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are in agreement with our previous observations, 22 which also showed that lifetime-captopril-treated SHR had decreased brain Ang II binding, suggesting a depressed angiotensinergic system in the brain. Our results are also consistent with those of Schelling and Felix, 32 who showed a decrease in the sensitivity of Ang II receptors to iontophoretically applied Ang II in septal neurons of SHRSP with lifetime captopril treatment. 32 In summary, lifetime oral captopril treatment prevented the development of hypertension in spontaneously hypertensive rats.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the observation that the drinking response to Ang II was also depressed suggested that decreased responsiveness may be related to a reduction in Ang II receptors in the brain. This was our finding in Ang II binding studies in the hypothalamus of captopril-treated SHR as compared with control rats and is consistent with findings of Schelling and Felix, 32 who reported that captopril treatment decreased Ang II receptor sensitivity to iontophoretically applied Ang II. In contrast to the central effects, peripheral responsiveness to Ang II and receptor binding kinetics of the peptide were significantly enhanced as a result of lifetime captopril treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the observations that the drinking responses to Ang II were also depressed suggest that the decreased responsiveness may be related to the reduction of Ang II receptors in the brain. The results are consistent with those of Schelling and Felix,7 who reported that lifetime captopril treatment decreased Ang II receptor sensitivity to iontophoretically applied AngLI.…”
Section: Discussionsupporting
confidence: 92%
“…2 Vasopressin and adrenocorticotropic hormone (ACTH) secretion and sympathetic tone are also enhanced. 3 - 4 Additional reports indicate that the pressor effects of centrally administered Ang II are increased in SHR, 3 6 the sensitivity to iontophoretically applied Ang II is enhanced, 7 and increases in the number of Ang II receptors are observed in areas of the brain that are integral to cardiovascular control. 8 •' The strongest evidence that brain Ang II may play a role in the pathogenesis of hypertension is that both short-term or long-term intracerebroventricular (i.c.v.)…”
mentioning
confidence: 99%